Health Care Utilization and Prescribing Patterns for Adult Eustachian Tube Dysfunction. (June 2019) - McCoul, Edward D.; Weinreich, Heather M.; Mulder, Hillary; Man, Li-Xing; Schulz, Kristine; Shin, Jennifer J.
Objective: Eustachian tube dysfunction (ETD) prompts >2 million adult visits in the United States annually. While disease prevalence and health care utilization are established for children, practice patterns for adults remain unknown. Our objective was to determine national resource utilization for adult ETD. Study Design: Cross-sectional study. Setting: National database sample. Subjects and Methods: The Truven Health MarketScan Databases (2010-2014) analytic cohort included health care encounters of patients ≥18 years of age with a diagnosis of ETD, otitis media with effusion, or tympanic membrane retraction. Visits associated with recent diagnoses of acute upper respiratory infection, head and neck cancer, or radiation therapy were excluded. Acute ETD (<3 months) and chronic ETD (≥3 months) were subgroups. Medication usage was quantified by class. Results: ETD was diagnosed for 1, 298, 987 patients, 11% of which was chronic. Over 92% of patients were seen in outpatient clinics, most often by otolaryngology (57%) for chronic ETD and by general medicine (49%) for acute ETD. Medications were frequently utilized, as 530, 146 (53.7%) patients received ≥1 prescription. Top prescriptions for chronic ETD included intranasal corticosteroids (22%), antibiotics (22%), oral corticosteroids (13%), and analgesics (6%). The overall annual cost of prescribed medications associated with visits in which either acute or chronic ETD was diagnosed exceeded $8.5 million for a mean of $80.78 per patient who filled a prescription. Conclusion: Adult ETD is frequently treated with several medication classes by a variety of provider types. Understanding the potential adverse effects and cost associated with these practices should be a priority.